Servant Leadership and Innovation: Dual Mediation through Psychological Safety and Technology Readiness - Sukma Putra (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid growth of Indonesia’s digital services sector has underscored the need for leadership styles that can enhance organizational resilience and foster innovation in a competitive environment. Startups in this sector often face high failure rates, making innovation a critical capability for survival and long-term growth. Against this backdrop, leadership practices that prioritize employee development and empowerment have become increasingly important. This study aims to examine the relationship between servant leadership and employee innovative behavior in Indonesia’s digital services sector, with particular attention to the mediating roles of psychological safety and technology readiness. A quantitative approach was employed, involving 150 respondents from digital service companies. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect effects among variables. The findings indicate that servant leadership exerts a significant positive influence on employee innovative behavior (β = 0.545, p < 0.001). Furthermore, psychological safety and technology readiness were found to function as significant mediators, with technology readiness demonstrating the stronger effect. These results highlight the importance of servant leadership in fostering innovation, particularly when combined with psychologically safe environments and proactive technological adoption.